MENCIPTAKAN ECOENTREPRENEURIAL CAMPUS MELALUI PEMBELAJARAN BERBASIS KEWIRAUSAHAAN - Bakar, M. Yunus Abu (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
College graduates are required to not only capable of acting as a job seeker, but also must be able to act as the creator of the work, both of which require entrepreneurial spirit. For a person, it is reflected in the variety of areas including leadership skills, independence (including the persistence), teamwork, creativity, and innovation. One possible cause of the weakness of the entrepreneurial spirit of college graduates is considered by the learning process in the college which is still limited to only a theory and has not been conditioned to build the entrepreneurial spirit in the activities of the industry and the real world of work. Other causes are lectures are still based on how learning is lecturer Teacher Center as a center of learning. Entrepreneurship education is also not limited to only certain subjects. Each course can basically be integrated into a variety of other fields. Each field can be combined with the entrepreneurial life. Thus, students have many options and not just to be a worker. Therefore, one of the future government policy is to make universities as Ecoentrepreneurial Campus, one term to develop its opportunities in college is ideal, the campus must show hospitality environment is equipped with an entrepreneurial infrastructure. Campus ecoentrepreneurial it can be combined with a game that trains the courage to make decisions, especially in the animation reaches the level of self-employment.Keywords: Ecoenterpreneurial campus